2005
DOI: 10.1161/01.cir.0000161822.83163.b6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Body Mass Index and Risk of Stroke in Apparently Healthy Women

Abstract: Background-Obesity is an escalating pandemic in the United States, and its association with coronary heart disease is well understood. Several studies have found positive associations between body mass index (BMI) and stroke in men, but the association with stroke and its subtypes is less clear in women. Methods and Results-This was a prospective cohort study among 39 053 women participating in the Women's Health Study. BMI was measured as self-reported weight (in kilograms) divided by height (in meters) squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(107 citation statements)
references
References 49 publications
7
98
1
1
Order By: Relevance
“…Some prospective studies have shown an increased risk for stroke with increasing BMI, particularly cerebral infarction [2,3,4,5,6,7,8]. Several studies also suggested that abdominal obesity, rather than general obesity, is associated with an increased risk for stroke [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some prospective studies have shown an increased risk for stroke with increasing BMI, particularly cerebral infarction [2,3,4,5,6,7,8]. Several studies also suggested that abdominal obesity, rather than general obesity, is associated with an increased risk for stroke [19].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity was categorized as a ‘less well documented or potentially modifiable risk factor’ in the guideline statement for health professionals from the Stroke Council of the American Heart Association [1]. Several studies have found a positive association between obesity and the risk of fatal and nonfatal stroke, particularly ischemic stroke [2,3,4,5,6,7,8]. Others have suggested a U-shaped association, with individuals at either extreme of the BMI distribution at high risk [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…3 In fact, risk for ischemic stroke increases almost linearly starting at a BMI of ≈20 and adults with a BMI of >30 kg/m 2 have about a 70% increased risk for ischemic stroke compared with patients with a BMI <25 kg/m 2 . 4,5 In this issue of Stroke, Mitchell et al 6 raise further concern about obesity by showing an association with increased stroke risk in a study composed exclusively of young adults. Mitchell et al 6 studied men and women aged 15 to 49 years who participated in 3 separate case-control studies.…”
Section: See Related Article P 1690mentioning
confidence: 99%
“…4,5 In this issue of Stroke, Mitchell et al 6 raise further concern about obesity by showing an association with increased stroke risk in a study composed exclusively of young adults. Mitchell et al 6 studied men and women aged 15 to 49 years who participated in 3 separate case-control studies.…”
mentioning
confidence: 99%
“…However, it should be noted that the majority of women in the WHI were healthcare professionals and thus may be better at self-reporting than the general population (Kurth et al, 2005). The following study by Cook et al (2012) confirms these findings in a multiethnic diverse female population.…”
Section: The Limitations Of Current Risk Prediction Models For Risk Ssupporting
confidence: 66%